Analysis of Indian Pharmaceutical Industry and Trade Competitiveness: Using Revealed Comparative Advantage (RCA) - Hooda, Devinder Singh; A, Anu (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: This paper examines the growth of the Indian pharmaceutical sector, the changing dynamics and the export competitiveness of therapeutic segments. Further, this study compared the export competitiveness of the therapeutic segments with that of the leading exporting countries. Trade-Related Aspects of Intellectual Property Rights (TRIPS) is considered an emerging point in India's pharmaceutical sector's history. Having skills in making off-patent drugs at low cost contributes to India becoming a pharmacy of the world. With the growing importance of the pharmaceutical industry in the economy and trade, it is essential to investigate India’s trade competitiveness with other countries. Materials and Methods: The study used Revealed Comparative Advantage (RCA) to analyse the international competitiveness of therapeutic segments with top exporting countries and to find the comparative advantages and disadvantages of therapeutic segments from 2000 to 2022. The assessment of the pharmaceutical sector is based on secondary data collected from the World Integrated Trade Solution (WITS). This classification is based on ITC chapter (30) for pharmaceutical products, heading (3004) given by the Directorate General of Commercial Intelligence and Statistics (DGCIS). This study used HS 1988/92 and selected India as the reporting country from 2000 to 2022. Results: The results indicate that India became more competitive post-TRIPS and patents significantly influenced exports. Further, comparative analyses with top exporting countries revealed that Indian therapeutic segments are more trade-competitive, have a stronger position than the USA and are closer to Germany. The study also found that the Indian pharmaceutical industry has a favourable trade balance and its therapeutic segments are more competitive than the overall pharmaceutical products. The analysis of RCA suggests that India’s advantage lies in therapeutic segments. Exports of Indian pharmaceuticals are positively correlated with TRIPS compliance. Conclusion: The study concludes that the overall CAGR of the pharmaceutical and therapeutic segments are growing at a healthy rate. However, de-segregating the timeframe showed that, from 2014 to 2022, the CAGR was not the same as the early period and lower than the overall CAGR. Moreover, on the global comparison of therapeutic segments, the study suggests that robust policies and export measures must be taken to compete with countries like Belgium, Switzerland, Ireland and Denmark. Active Pharmaceutical Drugs (APIs) need to be imported (the majority from China) to make the formulation drugs in India, leading to a high dependency on imports of APIs. Therefore, the study suggested that the government should also focus on producing active pharmaceutical drugs domestically, which can reduce the price of drugs in India.
Keywords: Export competitiveness; Patents; Pharmaceutical industry; Revealed Comparative Advantage